Prevention and Management of Venous Thromboembolic Disease in Cushing’s Syndrome: A Proposal based on a Case Report and Literature Review - Gutiérrez Restrepo, Johnayro; Plaza Tenorio, Maribel; Román González, Alejandro (Iatreia, 2025)
Introduction: Cushing’s syndrome is associated with multiple complications, among which thromboembolic disease is relatively frequent and contributes substantially to morbidity and mortality. Objectives: Conduct a review of the topic based on a clinical case. Methodology: A clinical case was presented, from which a review of the epidemiological and pathophysiological aspects was conducted; finally, a proposal for the management of venous thromboembolic disease based on available evidence in the medical literature was put forward. Conclusions: Cushing’s syndrome is associated with a high risk of thromboembolic events. Adequate management with thromboprophylaxis and anticoagulation as well as non-pharmacological measures are required to avoid complications in those affected.